Effects of butter oil and whey proteins addition on viscoelastic properties of confectionary Dulce de leche - Olivares, María Laura (2014)
The effect of butter oil and whey proteins addition on viscoelastic properties of confectionary Dulce de Leche was evaluated. A two factors experimental design (0-8 % p/v of butter oil and 0-1 % p/v of whey proteins) was analysed. Frequency sweep tests were carried out and for all formulations studied a weak gel like behavior was observed. Therefore, results were interpreted using a weak gel model for foods. It was observed that the rheological behavior of the sample with addition of whey proteins and butter oil is significantly different than the others because rheological units interact with greater strength. Even more, the sample without butter oil and with whey proteins addition is composed by less rheological units than the others. It is concluded that the whole addition of butter oil and whey proteins generates a stronger gel matrix, more appropriate for use in confectionary.